Training principles to advance expertise - Healy, A. F.; Kole, J. A.; Bourne Jr., L. E. (Frontiers in Psychology, 2014)
There are three forms of task engagement that are the basis of successful training for expertise—acquisition, retention, and transfer—and three corresponding goals of training—efficiency, durability, and generalizability. This paper reviews training conditions that facilitate acquisition, enhance retention, and promote transfer to contexts not encountered during training. Diligent practice under these training conditions can lead eventually to an elite level of performance or to expertise.